Brown-Vialetto-Van Laere syndrome: Clinical and neuroradiological findings of a genetically proven patient. Issue 1 (March 2014) - Bandettini Di Poggio, Monica; Monti Bragadin, Margherita; Reni, Lizia; Doria-Lamba, Laura; Cereda, Cristina; Pardini, Matteo; Roccatagliata, Luca; Rossi, Andrea; Schenone, Angelo
Abstract The Brown-Vialetto-Van Laere syndrome (BVVLS) is a rare neurological disorder characterized by progressive pontobulbar palsy, sensorineural deafness and mixed spinal and upper motor neuropathy. Mutations in the C20orf54 gene have been linked to the disease and recently we reported the first Italian case of a BVVLS family with an intriguing C20orf54 genotype. However, the pathomechanisms underlying BVVLS are still unknown. Here we present the particular disease course with partial response to immunosuppressive therapy of our BVVLS patient for whom we hypothesize that dysimmune factors may have played a role in disease physiopathology.